Adapting Intercultural Communication and Spanish Classes at Shanghai University during COVID-19: Zoom, WeChat, and Beyond - Bradford, Mitchell R (International journal of education and development using information and communication technology, 2021)
This paper will discuss how intercultural communication (ICC) and Spanish classes at the Sydney Institute of Language and Commerce (SILC)-Business School at Shanghai University were adapted to be conducted virtually during COVID-19. The platforms used included Zoom, WeChat, and pre-recorded videos of lessons. While the Spanish course met for short classes to practice speaking, the ICC course only discussed via messaging in a WeChat group. Both had pre-recorded videos of lessons. The merits and drawbacks of each of these will be discussed. Additionally, perceptions of these tools were collected via questionnaires with 25 Likert-scale items and 15 open-ended items conducted with the students of the courses and teachers of different subjects at SILC. Findings indicate that each have their strengths and weaknesses but could be used synchronously to achieve the best outcomes. For example, Zoom being used only for small groups to practice speaking and videos for lecturing. Interestingly, most teachers reported not using WeChat for teaching purposes despite the students being very familiar with it and finding it useful for several aspects. The paper ends with suggestions on how these methods can be used for classes after the pandemic, whether they are conducted online or in person.